2008
DOI: 10.1038/oby.2007.106
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Dysregulation in the Pancreas and Adipose Tissue of Mice Fed With a High‐fat Diet

Abstract: objective: In mice, endocannabinoids (ECs) modulate insulin release from pancreatic β-cells and adipokine expression in adipocytes through cannabinoid receptors. Their pancreatic and adipose tissue levels are elevated during hyperglycemia and obesity, but the mechanisms underlying these alterations are not understood. Methods and Procedures:We assessed in mice fed for up to 14 weeks with a standard or high-fat diet (HFD): (i) the expression of cannabinoid receptors and EC biosynthesizing enzymes (N-acyl-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
167
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 62 publications
19
167
2
5
Order By: Relevance
“…This conclusion is built on our findings of lower levels of 2-AG in AT in the obese The endocannabinoid system in adipose tissue MF Bennetzen et al individuals, low levels that increase/normalise in association with weight loss, and low levels of CB1 expression in SAAT in the obese group, which also increases after weight loss. The finding of low levels of ECs in SAT from obese subjects is well in line with studies in obese rodents, 31,32 demonstrating a pronounced reduction in subcutaneous EC in obese rodents, whereas the change in ECs in VAT was more modest after diet-induced obesity. Animal studies do indicate hyperactivity of the ECS in obesity in the intra-abdominal (epididymal) AT depot.…”
Section: Discussionsupporting
confidence: 72%
“…This conclusion is built on our findings of lower levels of 2-AG in AT in the obese The endocannabinoid system in adipose tissue MF Bennetzen et al individuals, low levels that increase/normalise in association with weight loss, and low levels of CB1 expression in SAAT in the obese group, which also increases after weight loss. The finding of low levels of ECs in SAT from obese subjects is well in line with studies in obese rodents, 31,32 demonstrating a pronounced reduction in subcutaneous EC in obese rodents, whereas the change in ECs in VAT was more modest after diet-induced obesity. Animal studies do indicate hyperactivity of the ECS in obesity in the intra-abdominal (epididymal) AT depot.…”
Section: Discussionsupporting
confidence: 72%
“…36,37 A higher endocannabinoid tone is detected in the visceral fat relative to the subcutaneous fat in both human and mice. 10,12,13 Treatment of rimonabant exhibits a preferential loss of abdominal fat over subcutaneous fat, 38 which was also observed in the treatment with BPR697. In this regard, repeated stimulation of fatty acid oxidation in addition to inhibition of lipid accumulation decreased abdominal fat mass and hepatic lipids, as observed in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…4--7 On the other hand, the CB1 receptor found in many peripheral tissues involved in metabolism, such as liver, adipose tissue, skeletal muscle, pancreas and the gastrointestinal tract, promotes anabolic pathways, such as de novo lipogenesis and glucose uptake, to regulate energy homeostasis. 5,8--11 The endocannabinoid system is dysregulated after chronic perturbation of energy balance, as can be seen in mice fed a high-fat diet, and in obese and diabetic patients, 10,12,13 thus contributing to the exacerbation of these disorders and the associated cardiometabolic indices.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16]18,21 It is, however, rather surprising in light of the findings by others showing that HF diets given to mice cause dysregulation of the ECS, either via alterations in the expression of CB 1 receptors, via alterations in the levels of endogenous ligands, or both. 17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs.…”
Section: Discussionmentioning
confidence: 99%